2022
DOI: 10.1111/acps.13471
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of treatments for rapid cycling bipolar disorder

Abstract: Objectives: Rapid cycling is a common and disabling phenomenon in individuals with bipolar disorders. In the absence of a recent literature examination, this systematic review and meta-analysis aimed to synthesise the evidence of efficacy, acceptability and tolerability of treatments for individuals with rapid cycling bipolar disorder (RCBD).Method: A systematic search was conducted to identify randomised controlled trials assigning participants with RCBD to pharmacological and/or non-pharmacological intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 93 publications
0
37
0
1
Order By: Relevance
“…This approach would enable a more precise characterization of the phenomenon within specific phases of the disorder. Sixth, it was not possible to control the results for clinically relevant patterns such as rapid‐cycling, 104 atypical and mixed features of depression, 74 lifetime treatment response (including harm) to antidepressants, atypical antipsychotics 105 or lithium, 106 post‐partum, 107 seasonal features, 108 functioning, 109 comorbid eating disorders, 110 borderline personality disorder 111 or substance use disorders 112 as such features may be either relatively frequent among people with BD and likely represent the expression of ED themselves or being modulated (and modulators) of ED anyway. Finally, most of the patients in those studies were on medication, which may influence the findings 113 …”
Section: Discussionmentioning
confidence: 99%
“…This approach would enable a more precise characterization of the phenomenon within specific phases of the disorder. Sixth, it was not possible to control the results for clinically relevant patterns such as rapid‐cycling, 104 atypical and mixed features of depression, 74 lifetime treatment response (including harm) to antidepressants, atypical antipsychotics 105 or lithium, 106 post‐partum, 107 seasonal features, 108 functioning, 109 comorbid eating disorders, 110 borderline personality disorder 111 or substance use disorders 112 as such features may be either relatively frequent among people with BD and likely represent the expression of ED themselves or being modulated (and modulators) of ED anyway. Finally, most of the patients in those studies were on medication, which may influence the findings 113 …”
Section: Discussionmentioning
confidence: 99%
“…Second, we focused on acute antimanic outcomes (week 3); therefore, our study findings cannot be generalised to the maintenance treatment phase of bipolar disorder 23 and rapid cycling bipolar disorder. 24 Third, we examined the variability in improvement of manic symptoms of active treatments to control; therefore, we only included placebo-controlled trials. Head-to-head RCTs were not included.…”
Section: Discussionmentioning
confidence: 99%
“…To address this unmet need, Strawbridge et al, for the first time, conducted a systematic review with meta-analysis of treatments for rapid cycling bipolar disorder, published in the current issue of Acta Psychiatrica Scandinavica. 14 They included a total of 30 randomized trials comprising 2266 patients with rapid cycling and analyzed the observed outcomes for each treatment arm separately as pooled estimates across studies, thus providing estimates of the change in illness severity within patients before and after treatment. While such a within-subject approach has the drawback that estimates do not directly reflect the effect of the treatment, because it is not possible to disentangle which proportion of the change was caused by the intervention or other factors, 15 it allowed the authors to include more studies.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…There is unfortunately no clear consensus regarding the optimal treatment for rapid cycling, and the available evidence has not been quantitatively synthesized. To address this unmet need, Strawbridge et al, for the first time, conducted a systematic review with meta‐analysis of treatments for rapid cycling bipolar disorder, published in the current issue of Acta Psychiatrica Scandinavica 14 . They included a total of 30 randomized trials comprising 2266 patients with rapid cycling and analyzed the observed outcomes for each treatment arm separately as pooled estimates across studies, thus providing estimates of the change in illness severity within patients before and after treatment.…”
mentioning
confidence: 99%